Geographical differentiation of the Polish foreign trade and the impact of the COVID-19 pandemic (Economic and Political Thought, 2020)
The aim of this paper is to present the structure of Poland’s trade withits main partners in 2015–2020. We argue that the geographical diversity ofPolish trade – a positive balance with the EU countries and a negative onewith other countries – results from the structure of imports and exports. Inturn, this structure depends on the category of commodity being traded in.Another important factor in the context of the economic order is the ease ofdoing business. However, the global economy, including the EU, has beenseverely affected by the coronavirus pandemic outbreak, which also has hadits impact on the Polish market: we can observe a significant weakening ofPolish foreign trade in the first quarter of 2020.In the first part of the paper, we analyse Poland’s foreign trade in theperiod 2015–2020. Going into detail, we discuss the diversification of tradewith regard to Poland’s major trading partners. For many years, Germany,the Czech Republic and the United Kingdom have been Poland’s main exportpartners.The categories of commodities that Poland trades in are recognised asthe main cause of the disproportion in the trade balance. Poland has beenachieving good export results due to the successively increasing geographicaldiversification of the directions of Polish trade expansion.
Keywords: foreign trade, COVID-19, Poland, EU, SITC, trade turnover